2018
DOI: 10.18632/oncotarget.24066
|View full text |Cite
|
Sign up to set email alerts
|

Bile acid metabolism regulated by the gut microbiota promotes non-alcoholic steatohepatitis-associated hepatocellular carcinoma in mice

Abstract: Gut microbiota plays a significant role in the development of hepatocellular carcinoma (HCC) in non-alcoholic steatohepatitis (NASH). However, understanding of the precise mechanism of this process remains incomplete. A new class steatohepatitis-inducing high-fat diet (HFD), namely STHD-01, can promote the development of HCC without the administration of chemical carcinogens. Using this diet, we comprehensively analyzed changes in the gut microbiota and its metabolic functions during the development of HCC in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
98
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 110 publications
(100 citation statements)
references
References 33 publications
1
98
0
Order By: Relevance
“…Fecal pellets were collected from each animal, the collected samples within the same group were, pooled and kept at À80 C freezer until DNA extraction. 33,34 The DNA extraction was done using the homogenized pooled samples and using the GeneJet Genomic DNA purication Kit (Thermo Scientic, cat. no.…”
Section: Microbiome Determination and Analysismentioning
confidence: 99%
“…Fecal pellets were collected from each animal, the collected samples within the same group were, pooled and kept at À80 C freezer until DNA extraction. 33,34 The DNA extraction was done using the homogenized pooled samples and using the GeneJet Genomic DNA purication Kit (Thermo Scientic, cat. no.…”
Section: Microbiome Determination and Analysismentioning
confidence: 99%
“…Additionally, FXR modulates the gut–vascular barrier by regulating the entry sites for bacterial translocation . In the setting of NAFLD and ALD, both altered BA metabolism and changes in microbiota composition have been found, which potentially promotes disease development . Recent studies have explored the effects of ursodeoxycholic acid (UDCA) on gut microbiome composition in healthy individuals and also in individuals with liver dysfunction .…”
Section: Introductionmentioning
confidence: 99%
“…COX‐2 overexpression and excessive PGE2 production were detected in HSCs of human noncirrhotic NASH, indicating that a similar mechanism could function in humans . A recent report showed that DCA also promotes HCC progression by activating the mammalian target of rapamycin pathway . It was found that a new class of a steatohepatitis‐inducing HFD, STHD‐01, could promote HCC without chemical carcinogen administration …”
Section: Dca and Nash‐associated Liver Cancermentioning
confidence: 99%
“…A recent report showed that DCA also promotes HCC progression by activating the mammalian target of rapamycin pathway . It was found that a new class of a steatohepatitis‐inducing HFD, STHD‐01, could promote HCC without chemical carcinogen administration …”
Section: Dca and Nash‐associated Liver Cancermentioning
confidence: 99%